Interior design practice: project management competency framework / Nur Maizura Ahmad Noorhani and Arniatul Aiza Mustapha - Ahmad, Noorhani; Mustapha, Arniatul Aiza (UiTM Press, 2021)
Currently, a role for a creative or visually appealing interior designer has also includes project management. One of the project's primary roles is for the interior design manager is to successfully deliver to the client. Additionally, project managers are measured for their capability to deal with day-to-to-day activities as well as projects. This study shares the required competencies project managers and interior designers to qualify as a project manager in the field of design. This paper examines the 27 competencies required of an interior project manager and highlights the value of competence in these three areas: functional, contextual, and behavioral. Competence as a project manager is assessed using questionnaires. The review and data collection of the results later helps support competency skills, which then diminishes the value of competency activities. From the analysis of the results, it follows that the project validity of the manager's knowledge increases project efficiency. Following the findings, new guidelines are implemented to further and more generally define the nature of the research.